2010
DOI: 10.4103/0973-3930.62598
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin variants detected by hemoglobin A1c (HbA1c) analysis and the effects on HbA1c measurements

Abstract: Background:Hemoglobin (Hb) A1c is a tool widely used to monitor long-term glycemic control in diabetic patients. The objective of our study is to compare the HbA1c values measured on high performance liquid chromatography (HPLC) and immunoassay in patients who were detected to have hemoglobin variant after HbA1c analysis.Materials and Methods:We compared the HbA1c values measured using the Arkray Adams A1c HA-8160 (HPLC method) and Roche Cobas Integra (immunoturbidimetric method) from diabetic patients who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Second, under the logistical constraints, HbA1c and FPG were used to diagnose DM instead of the oral glucose tolerance test recommended by the WHO [16]; these tests could be a practical option as a feasible method for detecting DM in seroprevalence surveys in settings with limited resources. Third, hemoglobinopathy, which is a relatively prevalent disorder in Southeast Asia, can compromise the consistency of results for DM diagnosis because it affects HbA1c levels [22, 23]. Therefore, in this study, we excluded one suspected case that demonstrated apparent discordance between HbA1c and FPG levels without laboratory testing for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, under the logistical constraints, HbA1c and FPG were used to diagnose DM instead of the oral glucose tolerance test recommended by the WHO [16]; these tests could be a practical option as a feasible method for detecting DM in seroprevalence surveys in settings with limited resources. Third, hemoglobinopathy, which is a relatively prevalent disorder in Southeast Asia, can compromise the consistency of results for DM diagnosis because it affects HbA1c levels [22, 23]. Therefore, in this study, we excluded one suspected case that demonstrated apparent discordance between HbA1c and FPG levels without laboratory testing for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…With the limited interpretation which can come from a single RBS and difficulty in obtaining a fasting blood sugar in a voluntary impromptu screening, there is considerable need for more contextualized strategies [23]. As access to point of care A1c testing is expanded in resource-constrained settings, it is hoped that questions about its accuracy in these populations can be addressed and subsequently be integrated into home-based screening and care to continue to improve the ease with which patients can be screened to confirm diabetes [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“… 8 Extending set target HbA1c values to this group of patients may be erroneous due to potential risk of hypoglycaemia. 9 …”
Section: Discussionmentioning
confidence: 99%